Pengaruh Realisasi Kompensasi Finansial Terhadap Kinerja Karyawan Dengan Tingkat Kedisiplinan Dan Kepuasan Kerja Sebagai Variabel Intervening Pada PT Perkebunan Nusantara VIII Bojongdatar - Alfarizi, Abdul Wahid (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2020)
Employee performance at PT Perkebunan Nusantara VIII Bojongdatar in 2019 decreased compared to previous years, this indicates that the employee's performance has not been maximized. This can be caused by the ineffective factor of realization of financial compensation. The purpose of this study was to examine and analyze the effect of the realization of financial compensation on employee performance through the level of discipline and job satisfaction as intervening variables. This research method uses quantitative methods using causality, which is looking for explanations in the form of a cause-and-effect relationship between several concepts or variables, the researcher collects primary data using a proportional random sampling technique in which the minimum sample size is multiplied by the number of indicators in this study the minimum sample size is measured. taken are 6 x 17 = 102 respondents and data analysis techniques with software Partial Least Square (PLS). The results showed that the realization of financial compensation had a direct effect on employee performance and there was an effect after being tested with the intervening variable on the level of discipline and job satisfaction.